The Influence of Work Motivation and Leadership Style On Employee Performance Through Job Satisfaction as A Mediating Variable at The Employment BPJS Sumbagut Regional Office - Wirandi Pranoto; Mesra B (International Publisher, 2024)
This study aims to look at the effect of work motivation and leadership style on employee performance through job satisfaction as a mediating variable at the Sumbagut Regional Office of Employment BPJS. This type of research uses qualitative methods, this research was conducted at the BPJS Employment Sumbagut Regional Office, the population used was 60 employees. The sample used was all the population of 60 employees with saturated samples being the sample technique. The data source used is primary data source and data collection by distributing questionnaires. This research model uses phat analysis and the measuring instrument is the smart PLS version 3.3.3 application. The results of this study are as follows: Leadership style has a positive and significant effect on job satisfaction with an original sample value of 0.276 and P values of 0.000. Leadership style has a positive and insignificant effect on employee performance with an original sample value of 0.102 and p values 0.615. Job satisfaction has a positive and significant effect on employee performance with an original sample value of 0.737 and p values of 0.000. Work motivation has a positive and significant effect on job satisfaction with an original sample value of 0.859 and p values of 0.000. Work motivation has a positive and insignificant effect on employee performance with an original sample value of 0.001 and p values of 0.999. Leadership style has a negative and insignificant effect on employee performance through job satisfaction indirectly with original sample results -0.199 and p values 0.095. Work motivation has a positive and significant effect on employee performance through job satisfaction with an original sample value of 0.630 and p values of 0.000.